The 2015 Mw 6.0 Mt. Kinabalu earthquake: an infrequent fault rupture within the Crocker fault system of East Malaysia - Wang, Yu (2017)
The Mw 6.0 Mt. Kinabalu earthquake of 2015 was a complete (and deadly) surprise, because it occurred well away from the nearest plate boundary in a region of very low historical seismicity. Our seismological, space geodetic, geomorphological, and field investigations show that the earthquake resulted from rupture of a northwest-dipping normal fault that did not reach the surface. Its unilateral rupture was almost directly beneath 4000-m-high Mt. Kinabalu and triggered widespread slope failures on steep mountainous slopes, which included rockfalls that killed 18 hikers. Our seismological and morphotectonic analyses suggest that the rupture occurred on a normal fault that splays upwards off of the previously identified normal Marakau fault. Our mapping of tectonic landforms reveals that these faults are part of a 200-km-long system of normal faults that traverse the eastern side of the Crocker Range, parallel to Sabah’s northwestern coastline. Although the tectonic reason for this active normal fault system remains unclear, the lengths of the longest fault segments suggest that they are capable of generating magnitude 7 earthquakes. Such large earthquakes must occur very rarely, though, given the hitherto undetectable geodetic rates of active tectonic deformation across the region.